Transparansi Angkasa Sebelum dan Sesudah Letusan Gunung Api : Kasus Angkasa Lembang Th. 1982 - Hakim Luthfi; Cecep Nurwendaya; Bambang Hidayat (Institute for Research and Community Services (LPPM) ITB, 1984)
Sari. Hasil pengamatan fotoelektrik bintang standar dengan refraktor Bamberg, di Obseryatorium Boscha, Lembang, pada periode Juli 1982, memperlihatkan koefisien ekstingsi angkasa lebih tinggi dibandingkan dengan koefisien ekstingsi yang diperoleh pada bulan Juni Juli 1983. Koefisien ekstingsi adalah ukuran transparansi angkasa. Makin besar koefisien absorpsi makin rendah transparansi. Berkurangnya transparansi di tahun 1982 diduga karena penambahan partikel stratosfer, yang berasal dari sisa letusan Galunggung. Abstract. Observations of photoelectric standard stars with the Bamberg refractor of the Bosscha Observatory, in July 1982 revealed abnormally high atmospheric extinction coefficients, as compared to that obtained in July 1983. It is thought that the increase of extinction in July 1982, was caused by the increase in number of small particles in the stratrosphere, The particles were remnants from the eruption of Mount Galunggung (ca. 90 km south east of the Observatory) which erupted weeks earlier.